MORPHOLOGY AND MORPHOMETRIC FEATURES OF THE SMALL INTESTINE IN WHITE LABORATORY RATS DURING POSTNATAL ONTOGENESIS - Allambergen Rasbergenov; Dilorom Adilbekova (Central Asian Journal of Medicine, 2025)
This study investigates the morphological and morphometric characteristics of the small intestine in white laboratory rats during postnatal ontogenesis, focusing on developmental changes from birth to adulthood. The small intestine, a critical organ for nutrient digestion and absorption, undergoes significant structural and functional transformations as the organism matures. Using histological and morphometric techniques, we examined the dynamics of changes in the mucosal layer, villi height, crypt depth, and muscular layer thickness in rats aged 1 to 90 days. The results revealed that the most pronounced changes occur during the first 30 days of life, characterized by rapid growth and differentiation of intestinal tissues. By the 60th day, the morphometric parameters stabilized, indicating the completion of major developmental processes. Histological analysis demonstrated an increase in villi height and crypt depth, reflecting enhanced absorptive and secretory capacities of the small intestine. These findings provide insights into the adaptive mechanisms of the small intestine during postnatal development and contribute to a deeper understanding of the organ’s functional maturation. The study underscores the importance of the early postnatal period in shaping the structural and functional integrity of the small intestine, with implications for comparative anatomy and developmental biology.